Profile of High School Students' Critical Thinking Skills in Chemistry Subjects - Firdaus Anisa Utami; Erfan Priyambodo (Universitas Negeri Yogyakarta, 2025)
Learning in the 21st century requires students to possess a range of skills to keep pace with technological developments. This research examined the critical thinking abilities of 10th-grade students at a high school in Sleman. The sample was obtained through purposive random sampling and comprised 35 students. The instrument employed in this study was an essay test developed using Ennis’s critical thinking indicators as the foundation.. The collected data were analysed using simple descriptive statistics. The research findings indicate that the critical thinking skills of 10th-grade students remain in the low range, with a score range of 13 to 88 and an average of 55.9.